GASTRÓPODES (MOLLUSCA) ASSOCIADOS AO FITAL DE MACROALGAS DA PRAIA DE BOA VIAGEM (PERNAMBUCO, BRASIL) - Xavier, Everthon de Albuquerque; Correia, Filipe Ramos; Rangel, Artur Fagner Tavares; Campos, Juliana Marta Pereira; Tavares, Rafael de Miranda; Fernandes, Múcio Luíz Banja; Silva, Andréa Karla Pereira da (Revista Nordestina de Zoologia, 2014)
This study aimed to understand the biodiversity of mollusks of the class Gastropoda associated phytal macroalgal Boa Viagem beach, coast of Pernambuco, Brazil. Two sampling were conducted at different times, a dry and a wet season, totaling 12 samples which were fixed in 4% formaldehyde and then sent to the laboratory of Zoology of FAFIRE where screening occurred and fauna identification. After that, was calculated the density, dominance and frequency of species. There was a higher density in the collection held in the dry season, and increased frequency and dominance of species Eulithidium affine. It was also possible to note the great biological diversity present in Boa Viagem beach, even being a beach with large human influence.